Web-Based Tourism Bus Rental Web-Based Tourism Bus Rental - Padova Bima Maldini; Ade Eviyanti (Universitas Muhammadiyah Sidoarjo, 2022)
Advances in information technology, encourage many people to create the latest innovations for humans in disseminating information and obtaining information. Information that used to take a lot of time but in this case can be accessed in a matter of seconds we can receive the information, and it is the company's obligation to provide this information so that it can be quickly and easily accepted by all consumers. Po MWD 555 has several units and types of buses, such as big buses, medium buses, which in the provision of this type of bus will be adjusted to the needs of the tenants. Inside the bus, facilities such as air conditioning, TV, blankets and pillows are also provided so that customers feel at home and comfortable when renting a bus. In this study, the author uses the Waterfall method as the process or flow of the research to be carried out. The test results of the applications that have been made get the results that all the features and functions of the system can run according to what has been designed. In addition, the author also tested using the UAT method to get a percentage value of 96% so it can be concluded that this application can be accepted by users.